Molecular dynamics simulations of a cyclotetramethylene tetra-nitramine/hydrazine 5, 5′-bitetrazole-1, 1′-diolate cocrystal. Issue 34 (20th June 2019) - Zhai, Pengfei; Shi, Chengying; Zhao, Shengxiang; Mei, Zongshu; Pan, Yinguang
Abstract : An energetic ionic salt-based cocrystal formation, HMX/HA·BTO, is predicted based on molecular dynamics simulations. Abstract : An energetic ionic salt (EIS)-based cocrystal formation, cyclotetramethylene tetra-nitramine (HMX)/hydrazine 5, 5′-bitetrazole-1, 1′-diolate (HA·BTO), is predicted based on molecular dynamics simulations. HA·BTO is a newly-synthesized environmentally friendly energetic ionic salt with good detonation performance and low sensitivity. Calculated powder X-ray diffraction patterns and intermolecular interactions deduce the formation of the new cocrystal structure. Radial distribution function analysis suggests that hydrogen bonds and van der Waals (vdW) forces exist between the H⋯O pairs of HMX and HA·BTO, while the hydrogen bonds between the H of HA·BTO and the O of HMX play a prominent role. The cohesive energy density and mechanical properties are also analyzed. The cohesive energy density of the HMX/HA·BTO cocrystal is larger than that of the composite of HMX and HA·BTO, indicating an improvement in crystal stability by cocrystalization. Compared to both HMX and HA·BTO, HMX/HA·BTO has smaller Young modulus, bulk modulus and shear modulus values, but larger K / G values and a positive Cauchy pressure, suggesting decreased stiffness and improved ductibility. Moreover, the calculated formation energy is −405.79 kJ mol −1 at 298 K, which implies that the proposed cocrystal structure is likely to be synthesized at ambient temperature. In summary, we have predicted an EIS-based cocrystal formation in which the safety and mechanical properties of HMX have been improved via cocrystalization with HA·BTO, and this provides deep insight into the formation mechanism of the EIS-based cocrystal.